"All of Belarus has come out onto the streets": exploring nationwide protest and the role of pre-existing social networks. Issue 1 (4th March 2022) - Mateo, Emma
ABSTRACT: During moments of nationwide mass mobilization, what distinguishes the towns and cities that rise in the first week from those that do not see protest? Taking the case of nationwide protests in Belarus in August 2020, this study employs an original protest event catalogue to investigate what drives mobilization in early-rising localities. I test hypotheses in the protest literature relating to whether pre-existing social networks, or pre-election campaign rallies, influence subsequent protest mobilization. The innovative use of Telegram data demonstrates the platform's value for social scientists studying protest. My results suggest that pre-existing social networks help drive mobilization in localities by facilitating communication, coordination, and engagement prior to protest onset, priming people to be ready when the moment of protest arrives. This article also highlights the impressive scale of nationwide mobilization in Belarus in 2020, and demonstrates that local networks were engaging in widespread opposition activity even before mass mobilization.